The eastern Asian 'Middle Palaeolithic' revisited: a view from Korea. (15th September 2016) - Seong, Chuntaek; Bae, Christopher J.
Abstract: Abstract : Is the Middle Palaeolithic an appropriate concept in eastern Asia? The issue has been debated for China in two recent papers in Antiquity (Yee2012 ; Li2014 ), which in turn responded to an earlier argument set out by Gao and Norton (2002 ). But does the Korean record offer a different perspective? Here, the authors argue that Korean archaeology, as with the Chinese record, provides no support for a distinct Middle Palaeolithic. Rather than seeking to validate an inappropriate chronological framework derived from European Palaeolithic research, emphasis should instead be placed on developing a regionally specific model of prehistory for eastern Asia. They conclude, akin to Gao and Norton (2002 ), that the East Asian Palaeolithic should be divided into two major cultural periods: Early and Late.